Feed intake, growth performance and digestibility of nutrients of goats fed with outdoor-grown hydroponic maize sprouts - Whay, Chuin Lim; Mohd Nadzir, Mohd Noor Hisham; Hiew, Mark Wen Han; Mamat @ Mat Nazir, Md Shuhazlly; Shohaimi, Shamarina (Universiti Putra Malaysia Press, 2022)
The study aimed to determine the effects of feeding outdoor-grown hydroponics maize sprouts (HMS) on the growth performance and digestibility of nutrients in goats. Three treatment groups (n = 5), group T1 (control), were fed 500 g concentrate, and Napier grass; T2, 500 g concentrate, and HMS, while T3 had sole feeding of HMS using a completely randomized design. The results showed that HMS had a better feed nutritive composition with the lower concentration of indigestible fibre (P<0.05) and higher concentration of crude protein (12.28%) compared to Napier grass (7.22%) (P<0.05). Goats in T1 and T2 fed with concentrate had a higher average daily gain (ADG) of 79 g/day and 48 g/ day rivalling goats fed with HMS (44 g/day) (P<0.05). Feed conversion ratio (FCR) was significantly better (P<0.05) in goats in T1 and T2 compared to T3. Goats in groups T1 and T2 showed significantly higher dry matter digestibility (69.27% and 63.95%, respectively) and crude protein digestibility (71.89% and 72.28%, respectively) compared to group T3. Sole feeding of HMS exerted a minor impact on growth performance in the animals. However, the HMS could potentially replace the conventionally planted sprouts in conjunction with commercial concentrate to improve the growth performance of the small ruminants.